2011
DOI: 10.1038/msb.2011.27
|View full text |Cite
|
Sign up to set email alerts
|

Strong negative feedback from Erk to Raf confers robustness to MAPK signalling

Abstract: This study shows that MAPK signalling is robust against protein level changes due to a strong negative feedback from Erk to Raf. Surprisingly, robustness is provided through a fast post-translational mechanism although variation of Erk levels occurs on a timescale of days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
211
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(232 citation statements)
references
References 58 publications
20
211
0
1
Order By: Relevance
“…In sum, here we found that post-transcriptional control of a master transcriptional regulator provides an efficient mechanism that assures canalized development and that stabilizes a transcriptional network during development and in adult animals. The role of post-transcriptional control in stabilizing the activities and levels of key activators of systems based on feedback loops has been previously proposed 46,47,51 , but to the best of our knowledge, our work constitutes the first theoretical and experimental example of this control principle.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In sum, here we found that post-transcriptional control of a master transcriptional regulator provides an efficient mechanism that assures canalized development and that stabilizes a transcriptional network during development and in adult animals. The role of post-transcriptional control in stabilizing the activities and levels of key activators of systems based on feedback loops has been previously proposed 46,47,51 , but to the best of our knowledge, our work constitutes the first theoretical and experimental example of this control principle.…”
Section: Discussionmentioning
confidence: 84%
“…It has been previously suggested that post-transcriptional control (for example, by miRNAs) could be used to diminish variability in biological systems [46][47][48][49][50][51] . In this context, we speculate that the high-transcriptional/high-turnover Clk profile stabilizes the circadian system by minimizing the consequences of transcriptional noise and/or by allowing rapid transcriptional feedback control.…”
Section: Resultsmentioning
confidence: 99%
“…Although both oncogenes activate the MAPK cascade, differences also exist: first, KRAS activates a number of further signal transducers in addition to BRAF, 43 and second, oncogenic KRAS, but not BRAF, is subject to strong additional feedback control within the MAPK cascade. 44 These differences may explain why BRAF-mutated tumors have distinct molecular features and therapeutic profiles compared with BRAF non-mutated tumors, including those that are KRAS mutated. 3 Similar to BRAF, oncogenic KRAS can also initiate serrated lesions in the mouse, 45 but in contrast to BRAF, tumor progression in KRAS-transgenic mice crucially depends on loss of the tumor-suppressor Ink4a/ARF, but not on Wnt/β-catenin activation.…”
Section: Discussionmentioning
confidence: 99%
“…Caco2-tet cells have previously been modified to express a second-generation tetracycline-regulated transactivator and transcriptional silencer. 44,55 Caco2-tet were transfected using Lipofectamine 2000 (Life Technologies, Darmstadt, Germany) as per the manufacturer's instructions, using tetracyclineinducible plasmids coding for GFP, or combinations of GFP with BRAF V600E or BRAF V600K . We used luciferase reporter constructs with multimerized ELK, FOXO3 or LEF/TCF sites.…”
Section: Cell Culturementioning
confidence: 99%
“…Negative feedback is a common feature of PK signaling systems. For example, activated ERK inhibits Raf by phosphorylation (30), and ligandinduced phosphatases (e.g., MAPK phosphatases and Sprouty proteins) negatively regulate MAPK activation (31,32). In this paper, we argue that negative feedback protects information transfer by these systems from the combined effects of basal activity and cell-to-cell variation in network componentry.…”
Section: Loss Of Negative Feedback Can Eradicate Information Transfer Bymentioning
confidence: 93%